Investigating an intervention to support computer simulation use in whole-class teaching. Issue 1 (2nd January 2016) - Rutten, Nico; van Joolingen, Wouter R.; van der Veen, Jan T.
Abstract : Going beyond simply measuring the effectiveness of a teaching approach with computer simulations during whole-class science instruction, we investigated the interaction between teachers and their students as well as searched for mechanisms in the pedagogical context related to teachers' implementation of the intervention. Our quasi-experimental design involved having five teachers teach Newtonian mechanics with computer simulations to parallel classes of their upper secondary students. In the "Accustomed" condition the teacher decided how the lesson would unfold; in the experimental condition the lesson unfolded according to a pattern designed for "Peer Instruction". We investigated the pedagogical interaction between teachers and their students, which was expected to be affected by the intervention's support for the teacher as well by the teacher's support for the students. Learning effects as revealed by gains from pretest to posttest to delayed posttest did not consistently favour either condition. Identified mechanisms occurring in the pedagogical context that could explain our findings include: teacher's sense of ownership of the lesson, familiarity with the intervention conditions, and resistance to change. Suggestions for future research related to the identified mechanisms are offered.